Generalized network design problems - Feremans, Corinne; Labbé, Martine; Laporte, Gilbert (European Journal of Operational Research, 2003)
Network design problems (NDP) consist of identifying an optimal subgraph of a graph, subject to side constraints. In generalized NDP, the vertex set is partitioned into clusters and the feasibility conditions are expressed in terms of the clusters. Several applications of generalized NDP arise in the fields of telecommunications, transportation and biology. The aim of this review article is to formally define generalized NDP, to study their properties and to provide some applications.